How perceived risk and animosity towards a destination may influence destination image and intention to revisit: the case of Rio de Janeiro - Loureiro, S. M. C.; Jesus, S. (Anatolia, 2019)
his research aims to explore how animosity and perceived risk influence the image of a destination in its three dimensions cognitive, affective and conative. The current study also examines how the three dimensions of image influence the intention to revisit a destination. Evidence from 402 tourists who visited Rio de Janeiro suggest that perceived risk negatively and significantly influences cognitive, affective and conative images. Animosity does not influence significantly cognitive image and this, in turn, does not predict tourists’ intention to revisit. Yet, animosity negatively and significantly influences affective and conative images.